Challenges and Opportunities of the Implementation Limited Face-to-face Learning in the Elementary School - Alfathin, Aulia; MajidNuur Wachid Abdul; Naldi, Wahyu; Nurkhotimah, Vidanisa; Masnur (International Conference on Elementary Education, 2022)
In several areas, schools have begun to implement limited face-to-face learning. This is because conditions in each region have started to improve, and the level of emergency has lessened. This situation depends on the ability of schools to organize face-to-face meetings. The limited face-to-face implementation should include the appropriate method to avoid a widespread outbreak of COVID-19 in elementary schools. The goal of this study was to ascertain the benefits and drawbacks of restricted face-to-face learning in elementary schools. This study used a qualitative approach and involved a case study approach. SDIT Al-Bina, Purwakarta Regency is the location of this research. (1) Observation; (2) in-depth interviews; and (3) documentation are used to acquire data. The following procedures were utilized in the data analysis: (1) data collection; (2) data reduction; (3) data presentation; and (4) conclusions (Miles et al., 2014). The findings of this study indicate that the difficulty in implementing limited face-to-face learning is the discipline required to ensure the health of every element of the school for it to avoid becoming a hub for the growth of COVID-19 or a school cluster. The possibility is to enhance learning competencies that were lost in the process of learning.